Novel Homozygous Deletion in STRADA Gene Associated With Polyhydramnios, Megalencephaly, and Epilepsy in 2 Siblings: Implications for Diagnosis and Treatment. (December 2018) - Nelson, Katherine; Jackman, Christopher; Bell, Jennifer; Shih, Chie-Schin; Payne, Katelyn; Dlouhy, Stephen; Walsh, Laurence
Mutations in the STE20-related kinase adaptor α ( STRADA ) gene have been reported to cause an autosomal recessive neurodevelopmental disorder characterized by infantile-onset epilepsy, developmental delay, and craniofacial dysmorphisms. To date, there have been 17 reported individuals diagnosed with STRADA mutations, 16 of which are from a single Old Order Mennonite cohort and share a deletion of exons 9-13. The remaining individual is of consanguineous Indian descent and has a homozygous single–base pair duplication. We report a novel STRADA gene deletion of exons 7-9 in 2 sisters from nonconsanguineous parents, as well as an improvement in seizure control in 1 sibling following treatment with sirolimus, an m-Tor inhibitor of potential benefit to patients with this genetic mutation.